2021
DOI: 10.3390/ijms22116083
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Contribution of Endometriosis to the Risk of Developing Hormone-Related Cancers

Abstract: Endometriosis is a common gynecological disorder that has been associated with endometrial, breast and epithelial ovarian cancers in epidemiological studies. Since complex diseases are a result of multiple environmental and genetic factors, we hypothesized that the biological mechanism underlying their comorbidity might be explained, at least in part, by shared genetics. To assess their potential genetic relationship, we performed a two-sample mendelian randomization (2SMR) analysis on results from public geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 41 publications
4
11
0
Order By: Relevance
“… 28 The molecular mechanisms underlying these associations are still largely unexplored. 29 The increased risk of various forms of malignancy and the lower average age at diagnosis of malignancy compared with the general population suggest an underlying dysregulation of tumor growth in these women and strengthen the hypothesis of a disturbed immune system. 28 However, there are no studies to date on women with a history of cancer and subsequent endometriosis diagnosis.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“… 28 The molecular mechanisms underlying these associations are still largely unexplored. 29 The increased risk of various forms of malignancy and the lower average age at diagnosis of malignancy compared with the general population suggest an underlying dysregulation of tumor growth in these women and strengthen the hypothesis of a disturbed immune system. 28 However, there are no studies to date on women with a history of cancer and subsequent endometriosis diagnosis.…”
Section: Discussionmentioning
confidence: 72%
“…Recent studies have found a link between endometriosis and certain types of malignancies, particularly ovarian cancer, breast cancer, skin melanoma and non‐Hodgkin’s lymphoma 28 . The molecular mechanisms underlying these associations are still largely unexplored 29 . The increased risk of various forms of malignancy and the lower average age at diagnosis of malignancy compared with the general population suggest an underlying dysregulation of tumor growth in these women and strengthen the hypothesis of a disturbed immune system 28 .…”
Section: Discussionmentioning
confidence: 95%
“…Overall, the "Medical Genetics, Genomics and Bioinformatics" series collected 28 articles and reviews. This 2021 Special Issue is focused on the analysis of cancer progression [12], genetics mechanisms of cancers [13,14], and bioinformatics theory development [15].…”
mentioning
confidence: 99%
“…Rueda-Martínez and colleagues [14] studied the genetic contribution to hormonerelated cancers development. The authors used genome-wide association studies (GWAS) to evaluate the genetic relationship between endometriosis and hormone-related cancers.…”
mentioning
confidence: 99%
“…The guest editors are happy to announce the Special Issue topic at MDPI IJMS on medical genomics ( ) and next BGRS-2022 conference in Russia ( ). We wish that the readers find these papers to be interesting and stimulating, and we are continuing to collect papers on gene expression regulation based on novel sequencing and computational approaches [ 25 ], omics technologies, networks, and pathway analysis [ 26 ].…”
mentioning
confidence: 99%